Social networks collaborating with Professors of a Confessional Private University - Saboya Rios, Nemias (2017)
The purpose of the study was to determine the level of knowledge, attitude and practice of social networks as an academic collaborative tool in Professors at the Universidad Peruana Unión. It was a quantitative approach, with a non-experimental, descriptive cross-sectional design. It used a sample of 100 Professors that using social networking as a collaborative tool in their academic activities, and an instrument was developed.The statistical results showed that 53% of Professors had a regular level and 45% have a poor level of social networks knowledge as a collaborative tool, being 89% the size of the least known application.On the other hand, in the attitude, 78% of them showed to have a good level, showing that Professors have favorable and ethical to use social networking behaviors. Finally, 64% had a regular level and 28% had a poor level of practice.The collaboration and information dimension showed better results in a 56% and 61%, respectively. In conclusion, Professors have a better attitude to use social networks as a collaborative academic tool, being the last dimension that enhances the proper use of social networks, but in the knowledge and practice,Professors arestill limited to make the most of these tools for the teaching-learning process